Caracterização do trabalho do bibliotecário no campo jurídico em Belo Horizonte - Regina Celia Rosa Rezende (2007)
The occurred transformations that took place in Brazil, in the last decades, surpass the economic dimension and extend to all human habitats, which is the imposition in the social, political, family and schooling fields, besides making significant changes in Law and in the universe of labor, which are specific areas of interest in this research. In the bulge of these transformations, citizenry have a greater change in respect of their rights and duties related to social aspects such as the right to housing, the access to culture, the ingression of women in the workforce, so on and so forth. This context of social relations caused the increase of judicial demands and the search for mediation of conflicts, that is to say that there is an amplification of the Law field creating its expansion and therefore the increase of documental mass thereto. Such reality, on its turn, has made a demand for correct organization and fast retrieval of this infinite number of documents, function to which the Librarian is a recognized professional by the field of Law as properly qualified for the job. The objective of this work is to analyze the job of the Librarian in the field of Law trying to comprehend and configure this niche of market although little surveyed by the Librarian in respect of work relations, ambient conditions and necessary formation that this performance should take in the most efficient manner, in addition to the perception that the Librarian and the professional of Law have this performance. The data for such analysis were acquired through semi structured interviews and analysis of secondary sources that allowed, on a proper basis, by theoretical explanation, conclude that in the Law field of Belo Horizonte, the Librarian is renowned and is acknowledged as a professional capable of a specific set of knowledge that are granted by their university basis which qualifies them to the organizing of juridical information. In spite of argumentation between the modifications of Library Science paradigm into the Science of Information, this research represents that the demand in the market is for qualification inherent to the Librarian.